Design, synthesis and evaluation of redox, second order nonlinear optical properties and theoretical DFT studies of novel bithiophene azo dyes functionalized with thiadiazole acceptor groups - Castro, M. Cidália R. (2012)
Two series of novel thermally stable second-order nonlinear optical (NLO) heterocyclic azo dyes 4-5 have been designed and synthesized. The two series of compounds were based on different combinations of acceptor groups (thiadiazole or arylthiadiazole electron-deficient heterocycles) linked to bithiophene which acts at the same time as a donor group and as a pi-conjugated bridge. The solvatochromic behavior of azo dyes 4-5 was investigated in several solvents of different polarity, while their thermal stability was evaluated using thermogravimetric analysis. Optimized ground-state molecular geometries and an estimation of the lowest energy single electron vertical excitation energies in DMF solutions were obtained using density functional theory (DFT). Their redox properties were studied by cyclic voltammetry, while hyper-Rayleigh scattering (HRS) was employed to evaluate their second-order nonlinear optical properties. The measured molecular first hyperpolarizabilities and the observed electrochemical behavior showed variations for the different acceptor systems used (thiadiazole or arylthiadiazole) and were also sensitive to the electronic acceptor strength of the substituents (R) linked to thiadiazole or arylthiadiazole heterocycles. Donor-acceptor arylthiadiazole-bithienyl diazenes exhibit the most promising thermal (Td = 237-305 ºC) and solvatochromic (beta = 1117-2503 cm-1) properties and second order nonlinear optical response (136-226 x 10-30 esu).